IMPLEMENTASI BIMBINGAN KONSELING DALAM PEMBINAAN AKHLAK PESERTA DIDIK DI MI AL-KHAIRIYAH KUPANG TEBA BANDAR LAMPUNG TAHUN AJARAN 2022/2023 - Sunandar, Berlian; Handoko, Cipto; sunaryo (UNISAN JURNAL, 2023)
Implementation of counseling guidance in fostering student morals is an educational process that focuses on changing the morals and behavior of students to behave well and have good morals. The implementation of counseling guidance in moral development for students at MA Yasmida Ambarawa, Pringsewu Regency has been carried out well. Guidance and Counseling is an integral activity that cannot be separated. The word Guidance (Guidance) is always coupled with Counseling as a compound word, Counseling which is one of the Guidance techniques is often said to be the core of all services and Guidance. Data collection methods are carried out using observation, interview and documentation methods. In the analysis carried out the steps of data reduction, data presentation and drawing conclusions. As for analyzing by way of inductive thinking. Based on the data obtained, the results of research on the implementation of counseling guidance in the moral development of students at MA Yasmida show a fairly good and significant level of change, as can be seen from the students always following counseling guidance and moral development using methods of understanding, advice, motivation, encouragement. and habituation. So that slowly can change the nature and habits of students for the better